Effects of inflows on air entrainment in hydraulic jumps below a gate. Issue 2 (4th March 2017) - Takahashi, Masayuki; Ohtsu, Iwao
ABSTRACT: The characteristics of air entrainment in hydraulic jumps below a sluice gate were systematically investigated. The air entrainment region is divided into the advective diffusion region and the breaking region. For the advective diffusion region, it was found that the air concentration for a fully developed inflow is larger than that for an undeveloped inflow under a given inflow Froude number. For a partially developed inflow, the air concentration in the advective diffusion region depends on the boundary layer development of the supercritical inflow. The air concentration in the breaking region is nearly independent of the inflow conditions of the boundary layer development. Regarding the effect of the inflow Froude number, the air concentration in both the advective diffusion and breaking regions increases with the inflow Froude number under a given boundary layer development. The air entrainment mechanism in jumps is explained for both the advective diffusion and breaking regions.